2018
DOI: 10.1007/s00281-018-0678-9
|View full text |Cite
|
Sign up to set email alerts
|

Intricate relationships between naked viruses and extracellular vesicles in the crosstalk between pathogen and host

Abstract: It is a long-standing paradigm in the field of virology that naked viruses cause lysis of infected cells to release progeny virus. However, recent data indicate that naked virus types of the Picornaviridae and Hepeviridae families can also leave cells via an alternative route involving enclosure in fully host-derived lipid bilayers. The resulting particles resemble extracellular vesicles (EV), which are 50 nm–1 μm vesicles released by all cells. These EV contain lipids, proteins, and RNA, and generally serve a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 116 publications
0
28
0
Order By: Relevance
“…However, there is a risk of co-isolating pathogens with EVs, such as viruses that can have similar biophysical properties to EVs. Viruses may also be internalized into EVs as a route of spreading and immune evasion (116). In addition, studies have reported EV-mediated transfer of oncogenic molecules from tumor cells to normal cells (117).…”
Section: Evs In Immunotherapymentioning
confidence: 99%
“…However, there is a risk of co-isolating pathogens with EVs, such as viruses that can have similar biophysical properties to EVs. Viruses may also be internalized into EVs as a route of spreading and immune evasion (116). In addition, studies have reported EV-mediated transfer of oncogenic molecules from tumor cells to normal cells (117).…”
Section: Evs In Immunotherapymentioning
confidence: 99%
“…Various naked viruses, such as Picornaviridae and Hepeviridae , can escape infected cells already in the prelytic phase of infection, via packaging and release within EVs ( Figure 4 ) [ 84 , 85 ]. This stealth mode prevents viruses from being neutralized by antibodies, but these virions also become dependent on EV-targeting pathways to infect new cells, as they are cloaked by a host-derived membrane.…”
Section: Integrins Control Uptake Of Extracellular Vesicles and Virusmentioning
confidence: 99%
“…Around the same time, in vitro studies showed that miRNAs and mRNAs are exported from cells in extracellular vesicles (EVs). These can transfer the RNAs to other cells where they mediate changes in gene expression (Skog et al, 2008;Valadi et al, 2007). The combination of these discoveries has led to an explosion of interest in the translational applications of EVs, and their miRNA cargos, over the last 10 years.…”
Section: Extracellular Small Rnas In Mammalsmentioning
confidence: 99%